Factors Affecting Satisfaction and Revisit-intention of Pilgrimage Tourists: Bà Chúa Xứ Shrine in Vietnam - Bang Nguyen Viet (The international journal of religious tourism and pilgrimage, 2021)
This study aims to define and measure key factors of the satisfaction and revisit-intention of pilgrimage tourists to Bà Chúa Xứ Shrine in Vietnam. The study involved both qualitative and quantitative methods: (i) qualitative research was carried out through focus group discussions with pilgrimage tourists, and (ii) quantitative research was conducted through interviews with 288 pilgrimage tourists. The results showed that intentions to revisit the Ba Chua Zu Shrine was directly affected by satisfaction, destination image, cultural contact, and spirituality. The results reveal that pilgrimage destination image, spirituality and cultural contact had positive and direct significant influences on revisit-intention and via adaptive satisfaction as a mediating influence mechanism. The findings provide strong evidence to tourism administrators that destination image and cultural contact, in particular, improve pilgrim-tourist satisfaction and intent to return. This has implications for those in the tourism industry, including destination marketers, government officials, and site managers.